2015
DOI: 10.1186/s12871-015-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Airtraq laryngoscope and the GlideScope for double-lumen tube intubation in patients with predicted normal airways: a prospective randomized trial

Abstract: BackgroundThe Airtraq laryngoscope and the GlideScope are commonly used in many airway scenarios. However, their features have not been fully described for double-lumen tube intubation. A prospective randomized study was designed to compare their intubation performances in thoracic surgery patients.MethodsSeventy ASA physical status I and II patients with predicted normal airway were scheduled for thoracic surgeries with double-lumen tube intubation. They were randomly assigned to one of two groups and intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Previous study [34] reported that the Airtraq had a shorter intubation time for DLT intubation than the Glidescope. In support, our study found that the Airtraq DL is superior to the McGrath Series 5 with regard to intubation time, although there were no differences in glottic exposure time between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [34] reported that the Airtraq had a shorter intubation time for DLT intubation than the Glidescope. In support, our study found that the Airtraq DL is superior to the McGrath Series 5 with regard to intubation time, although there were no differences in glottic exposure time between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…For blinding, given that different devices were used in almost all RCT studies, all studies (100%) were evaluated as high risk in blinding of participants and personnel to the intervention of the studies (performance bias). Eight studies (35%) that reported blinding of the outcome assessors were assessed as having unclear risk of bias [7,8,25,[27][28][29][30][31], and the other…”
Section: Risk Of Bias Assessment See Figmentioning
confidence: 99%
“…Success rate of the first attempt intubation of DLT. Four groups of devices from 21 studies were available for the analysis [1,7,8,17,18,20,[24][25][26][27][28][29][30][31][32][33][35][36][37][38][39]. Eligible comparisons in the NMA are shown in Figs 3A and 4A.…”
Section: Primary Endpointmentioning
confidence: 99%
“…We recruited 33 publications demonstrating the use of different VL for placement of DLT. [ 5 7 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yi et al . [ 28 ] have reported a shorter time to DLT intubation with the use of the Airtraq ® than with the GlideScope ® , despite the associated comparable success rate at the first attempt and difficult intubation score [ Table 3 ].…”
Section: Resultsmentioning
confidence: 99%